A new method of prenatal alcohol classification accounting for dose, pattern and timing of exposure: improving our ability to examine fetal effects from low to moderate alcohol. Issue 11 (19th October 2009) - O'Leary, C M; Bower, C; Zubrick, S R; Geelhoed, E; Kurinczuk, J J; Nassar, N
Abstract : Background: When examining the association between prenatal alcohol exposure and fetal effects, the timing and intensity of exposure have been ignored in epidemiological studies. The effect of using dose, pattern and timing of consumption ("composite" method) was investigated in this study, to examine the association between prenatal alcohol exposure and fetal effects. Methods: The composite method resulted in six categories of exposure (abstinent, low, moderate, binge <weekly, binge 1–2×/week and heavy). The odds of language delay and child behaviour problems were calculated for the composite method and then compared with an analysis using averaged estimates of <1 and 1+ drinks per day and with stratification by quantity ignoring dose per occasion. Data used for the analyses were from a 10% random sample of non-Indigenous women delivering a live infant in Western Australia (1995–1997). Participants from the 1995-1996 cohort were invited to participate in an 8-year longitudinal survey (78% response rate n=2224; 85% were followed-up at 2 years, 73% at 5 years and 61% at 8 years). Results: The effect of moderate and binge levels of exposure was only evident with the composite method; anxiety/depression following first-trimester moderate exposure (OR 2.24, 95% CI 1.16 to 4.34), and following late pregnancy moderate (aggressive behaviour OR 1.93, 95% CI 0.91 to 4.09) and binge (language delay OR 3.00, 95% CI 0.90 to 9.93) exposures. Results for heavy levels of exposure were similar with each method. The estimates for late pregnancy were imprecise due to small numbers. Conclusion: The composite method of classification more closely reflects real-life drinking patterns and better discriminates maternal drinking than the other methods, particularly low, moderate and binge levels.